Immunization-Induced Syncopal Attacks - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The clinical features and morbidity of a total of 697 cases of syncope after vaccination reported to the national Vaccine Adverse Reporting System were analyzed at the Center for Biologics Evaluation and Research, Food and Drug Administration, Rockville, Md.